COST EFFECTIVENESS ANALYSIS OF LETROZOLE VERSUS TAMOXIFEN IN EARLY-STAGE BREAST CANCER FOR POSTMENOPAUSAL WOMEN: SYSTEMATIC REVIEW - Lucia Shinta Ratnaningtyas; Prof.Dr. Tri Murti Andayani, Sp.FRS; Dr. apt. Dwi Endarti, S.F., M.Sc. (Universitas Muhammadiyah Purwokerto, 2026)
ABSTRACT Background:Breast cancer remains a major global health challenge, not only because of its clinical implications but also due to the increasing financial burden associated with its treatment. As such, cost-effectiveness analysis (CEA) plays a crucial role in supporting evidence-based decisions that optimize the use of healthcare resources. In postmenopausal women diagnosed with hormone receptor-positive early breast cancer, tamoxifen and letrozole are frequently prescribed endocrine therapies. Although letrozole has demonstrated superior efficacy in lowering recurrence rates and enhancing survival outcomes, its use is accompanied by higher treatment costs and a distinct profile of adverse effects. Objectives:This review aims to systematically examine and integrate current findings on the cost-effectiveness of letrozole versus tamoxifen in treating early-stage breast cancer in postmenopausal patients. Methods:A structured literature review was conducted in April 2025 across three major academic databases: PubMed, ScienceDirect, and SpringerLink. The selected studies were assessed for methodological rigor and potential bias using the CHEERS checklist. Five publications met the eligibility criteria and were included for data extraction and analysis. Results:All included studies reported that letrozole provided greater clinical benefit compared to tamoxifen in terms of reducing recurrence and extending disease-free survival in the target population. However, these clinical gains were linked to increased treatment costs and a unique spectrum of side effects. While letrozole was associated with a higher risk of bone and cardiovascular events, it posed a lower risk of endometrial cancer and thromboembolism than tamoxifen. Economic evaluations from various countries—namely China, Canada, the USA, the UK, and Germany—consistently found that letrozole led to greater quality-adjusted life years (QALYs). Moreover, its incremental cost-effectiveness ratios (ICERs) generally remained within acceptable national thresholds. Conclusion:For postmenopausal women undergoing adjuvant treatment for early-stage hormone receptor-positive breast cancer, letrozole offers a cost-effective alternative to tamoxifen. Despite its higher direct costs, its improved clinical efficacy supports its broader adoption in diverse healthcare systems. Keywords: Letrozole, Tamoxifen, Cost-effectiveness, Early-Stage Breast Cancer, Postmenopausal.